2013
DOI: 10.1038/ni.2670
|View full text |Cite
|
Sign up to set email alerts
|

The scavenger receptor SCARF1 mediates the clearance of apoptotic cells and prevents autoimmunity

Abstract: Clearance of apoptotic cells is critical for control of tissue homeostasis however the full range of receptor(s) on phagocytes responsible for recognition of apoptotic cells remains to be identified. Here we show that dendritic cells (DCs), macrophages and endothelial cells use scavenger receptor type F family member 1 (SCARF1) to recognize and engulf apoptotic cells via C1q. Loss of SCARF1 impairs uptake of apoptotic cells. Consequently, in SCARF1-deficient mice, dying cells accumulate in tissues leading to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
175
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 50 publications
5
175
0
Order By: Relevance
“…Blockage of SCARF1 by a blocking antibody resulted in a significant reduction in phagocytosis. A similar mechanism has been shown in uptake of apoptotic cells (Ramirez-Ortiz et al, 2013) by dendritic cells. Not only did SCARF1-deficient mice show a despaired removal of apoptotic cells, but also with time Ramirez-Ortiz et al were able to detect autoantibodies typical for SLE in those SCARF1-deficient mice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Blockage of SCARF1 by a blocking antibody resulted in a significant reduction in phagocytosis. A similar mechanism has been shown in uptake of apoptotic cells (Ramirez-Ortiz et al, 2013) by dendritic cells. Not only did SCARF1-deficient mice show a despaired removal of apoptotic cells, but also with time Ramirez-Ortiz et al were able to detect autoantibodies typical for SLE in those SCARF1-deficient mice.…”
Section: Discussionmentioning
confidence: 77%
“…The exposure of phosphatidylserine (PtdSer) on the cell surface is a hallmark feature of apoptosis (Fadok et al, 2001) and several factors have been shown to be involved in uptake of apoptotic cells by binding to PtdSer, such as brain-specific angiogenesis inhibitor 1 (BAI1) (Park et al, 2007) and factors of the T-cell immunoglobulin mucin (TIM) family (Kobayashi et al, 2007). In addition, factors such as scavenger receptor 1 (SCARF1; originally called scavenger receptor expressed by endothelial cell 1, SREC-1) have been shown to facilitate phagocytosis of apoptotic cells through PtdSer-independent pathways (Ramirez-Ortiz et al, 2013). Although uptake of apoptotic cells has been focus of intensive research, little is known about the mechanisms of AdMP uptake.…”
Section: Phagocytosis Of Admps Is Dependent On Scarf1mentioning
confidence: 99%
“…Phagocytosis and macropinocytosis are closely related processes (Swanson, 2008(Swanson, , 2014, however, the regulatory architecture of these processes are not fully understood (Bloomfield et al, 2015). These processes are triggered by the interaction between the particles and various kinds of receptors (Jang et al, 2009;Ramirez-Ortiz et al, 2013) As for CNTs, phagocytosis of SWCNTs by macrophages (Dong et al, 2013) and macropinocytosis of MWCNTs through macrophage receptor with collagenous structure (MARCO) (Hirano et al, 2012) have been reported, while the interaction of CNTs with scavenger receptors (ScRs), which are important for both phagocytosis and micropinocytosis, has also been reported (Wang et al, 2012). The surface modification, size, and shape of the CNTs or their agglomerates may affect their internalization pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, the general opinion was that scavenger receptors are highly atherogenic by producing massive cholesterol depositions in the blood vessel intima 23,55) . Today, it is known that scavenger function also regulates apoptotic cell clearance, thus maintaining vascular wall homeostasis 56) . However, further in vitro experiments showed that macrophages from CXCL16-deficient mice internalize apoptotic thymocytes equally well compared with those in control mice, which brought into question the proposed atheroprotective mechanism.…”
Section: -1 Cxcl16 Gene Polymorphisms and Circulating Levels As Potmentioning
confidence: 99%